Boisguilbert: A Neglected Precursor of Aggregate Demand Theorists: Reply - McDonald, S. L. (Quarterly Journal of Economics, 1956)
Journal Article Boisguilbert: A Neglected Precursor of Aggregate Demand Theorists: Reply Get access Stephen L. McDonald Stephen L. McDonald University of Texas Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 70, Issue 1, February 1956, Pages 165–166, https://doi.org/10.1093/qje/70.1.165-a Published: 01 February 1956